Fundamentals of Entrepreneurship (ENT300) : McDonald's / Afiq Fakhrul Ismail … [et l.] - Ismail, Afiq Fakhrul; Abdul Halil, Muhammad Ariff Aiman; Mohamed Faruk, Amar Mohamed Fadhilah; Ahmad Hasbie, Shahrul Izzat; Sudin, Alma’ Ashsyahir (2019)
McDonald's Restaurant started its business on 1940 in San Bernardino, California, United States. McDonald's Restaurant have been founded by Richard and Maurice McDonald. McDonald's has been serving over 69 million customers daily, in over 100 countries including Malaysia. McDonald's Restaurant started its business and operation in Malaysia on April 1982, at Jalan Bukit Bintang, Kuala Lumpur. In this segment, we study about among the biggest food chains industry in the whole world, which is McDonald's Restaurant, which located at Matang Jaya, Kuching.